Implementasi Teori Belajar Behavioristik Dalam Proses Pembelajaran - Miftahul Huda; Ach. Fawaid; Slamet Slamet (LPPM Politeknik Pratama, 2023)
Behavioristic theory is important to study in the learning process, because this theory is easily applied in educational learning in Indonesia. Learning theory is a combination of interconnected principles and explanations of a number of facts and discoveries related to learning events. This study reviews behavioristic theory and implementation in learning. The research method used is qualitative with a library research approach. Literature research is carried out by collecting information through the literature, then recording and processing the data that has been obtained. The result of this study is that the main focus in behavioristic learning theory is visible behavior and the external causes that stimulate it. Learning is a change in behavior as a result of experience. Learning based on behavior is obtained from environmental conditioning. This conditioning occurs through interaction with the environment, thus in learning behavior there is a close relationship between behavioristic reactions and the stimulus.